Innovative approaches in the organization student learning - Sh.B. Akhmedova (Proceedings of The ICECRS, 2019)
This paper makes analyses of the innovative approaches in the organization student learning. On this case, research gets points of both theoretical and methodological aspects to get better results. It concludes with the vivid results to make further analyses in the future investigations.